The pursuit of the ‘Dead Bandit’: a decolonial analysis of the persecution of the marginalized in Brazil - Cavalcanti, Roxana Pessoa (Critical criminology, 2022)
This article examines how the persecution of dissenting and marginalized populations in Brazil has intensified under the banner of crime control since the rise of the far-right to mainstream politics. Through decolonial lenses (Walsh and Mignolo 2018; Dimou 2021), it explores the ways in which anti-human rights discourses and Brazil’s myth of racial democracy relate to the legacy of colonialism in the experiences of urban poor and racialized communities. The aims of this work are to interrogate social relations and critically engage with the intensification of authoritarian neoliberal forms of governance. Reflecting on examples, such as the persecution and criminalization of political opponents, this article sheds light on examples of how coloniality is continuously reproduced in the politics of backlash that have become globally prevalent. The politics of backlash, as a variant of contested politics, often fuelled by anger and resentment, are central in the construction of retrograde and discriminatory transformations (Alter and Zürn 2020). By examining cases in Brazil, the article offers an analysis of how ‘coloniality’ (Quijano 1992; Walsh and Mignolo 2018) enriches critical understandings of the inequalities and discourses that operate to dispossess, silence, persecute and criminalize thousands of people.